2014
DOI: 10.1016/j.hkjot.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rhythmic Auditory Stimulation during Hemiplegic Arm Reaching in Individuals with Stroke: An Exploratory Study

Abstract: Objective/Background This study investigated the effects of rhythmic auditory stimulation (RAS) on muscle activity and elbow motion during arm reaching with hemiplegic arm in participants with stroke. Methods Sixteen adults with stroke who resided in a community were recruited in this study. The RAS consisted of sound emitted from a digital metronome. While sitting upright in a chair, participants reached their arms towards a target (a switch on a table) both with and without RAS. The three-dimensional motion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Further, a sub-group analysis for only rhythmic auditory cueing revealed a similar positive medium effect size with negligible heterogeneity (g: 0.37, 95% C.I: 0.01–0.72, I 2 : 0%, p > 0.05). Further sub-group analysis was not performed because two studies did not include a training regime ( 112 , 124 ), and one study analyzed the effects of real-time auditory feedback ( 118 ).…”
Section: Resultsmentioning
confidence: 99%
“…Further, a sub-group analysis for only rhythmic auditory cueing revealed a similar positive medium effect size with negligible heterogeneity (g: 0.37, 95% C.I: 0.01–0.72, I 2 : 0%, p > 0.05). Further sub-group analysis was not performed because two studies did not include a training regime ( 112 , 124 ), and one study analyzed the effects of real-time auditory feedback ( 118 ).…”
Section: Resultsmentioning
confidence: 99%
“…The sEMG signals were recorded through disposable AgCl electrodes by the 8-channel wireless sEMG system (Myo MUSCLE, Noraxon, USA Inc., Scottsdale, AZ, United States) (Mackala et al, 2013;Kim et al, 2014). The electrodes were placed on the affected biceps and the triceps.…”
Section: Parameters Of Semgmentioning
confidence: 99%
“…The proposed theory on RAS's therapeutic effects include the regulation of spatiotemporal and force parameters with specification of the dynamics of a movement and reduction Abbreviations: ADL, activities of daily living; BI, Barthel Index; CID, clinical important difference; FMA-UE, Fugl-Meyer Assessment-Upper Extremity; MMSE, Mini-Mental State Examination; RAS, rhythmic auditory stimulation; RMS, root mean square; RS, reticulospinal; sEMG, surface electromyography; WMFT, Wolf Motor Function Test. of variability via the rhythmic cues, thus achieving the optimal movement pattern with repetitive exercise (Thaut et al, 2002;Thaut et al, 2009;Kim et al, 2014). Also, the rhythmic auditory cues may help with motor priming, facilitate movement anticipation and preparation, and potentially bypass damaged areas through the activation of alternative pathways (Yoo and Kim, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Results displayed that reaching significantly improved more in the RAS group. The researchers documented that the RAS participants scored a shorter movement time, reduced change in acceleration, increased elbow extension range of motion, exhibited more muscle activation of the triceps, and reduced co-contraction ratio of affected arm (Kim et al, 2014). In short, the RAS group demonstrated more efficient reaches than the control group.…”
Section: Sound and Movementmentioning
confidence: 99%
“…In another context, a study found that rhythmic sound enhanced upper extremity reaching in clients with hemiplegia (Kim et al, 2014). Researchers stated that rhythmic auditory stimulation (RAS) activates the cerebral cortex, basal ganglia, and cerebellum, and travels through the autonomic nervous system through the brainstem and spinal cord (Kim et al, 2014). Consequently, muscles activate and coordinate as the body syncs with the auditory rhythm.…”
Section: Sound and Movementmentioning
confidence: 99%